Orthodontic camouflage treatment using a passive self-ligating system in skeletal Class III malocclusion - Fransiska Monika; Retno Widayati (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: The treatment options for adults with skeletal Class III malocclusion can be dentoalveolar compensation, also known as orthodontic camouflage, or orthognathic surgery. Camouflage treatment can be carried out with teeth extractions, distalisation of the mandibular dentition, and use of Class III intermaxillary elastics. However, intermaxillary elastics as anchorage has its own risk–benefit. Purpose: To explain that camouflage treatment with teeth extractions can be performed in a mild to moderate skeletal Class III malocclusion using intermaxillary anchorage with elastics, while minimising the deleterious effects and achieving a satisfactory treatment outcome. Case: Our patient was a 25-year-old female who had a skeletal Class III pattern, with normal maxilla and a protruded mandible. She had a straight facial profile with a Class III canine and molar relationship on her right and left sides. Anterior crossbite was also present with crowding on both the maxilla and the mandible. Case Management: The treatment plan was carried out with dentoalveolar compensation by extracting teeth. Extraction of the lower first premolars was conducted to eliminate the crowding and correct the anterior crossbite. The mandibular incisors were retroclined and the maxillary incisors were proclined with dentoalveolar compensation. Passive self-ligating system was used with standard torque prescription, intermaxillary anchorage, and no additional appliances for anchorage control. Class I canine and incisor relationship were both achieved at the end of the treatment, while maintaining the Class III molar relationship. Conclusion: Orthodontic camouflage treatment in an adult patient using a passive self-ligating system and intermaxillary anchorage can improve facial profile and improve dental occlusion.